Development of lanthanum strontium cobalt ferrite composite cathodes for intermediate- to low-temperature solid oxide fuel cells - Baharuddin, Nurul Akidah; Abd Rahman, Hamimah; Muchtar, Andanastuti; Sulong, Abu Bakar; Abdullah, Huda (Springer International Publishing, 2013)
Solid oxide fuel cells (SOFCs) offer high energy conversion, low noise, low pollutant emission, and low processing cost. Despite many advantages, SOFCs face a major challenge in competing with other types of fuel cells because of their high operating temperature. The necessity to reduce the operational temperature of SOFCs has led to the development of research into the materials and fabrication technology of fuel cells. The use of composite cathodes significantly reduces the cathode polarization resistance and expands the triple phase boundary area available for oxygen reduction. Powder preparation and composite cathode fabrication also affect the overall performance of composite cathodes and fuel cells. Among many types of cathode materials, lanthanum-based materials such as lanthanum strontium cobalt ferrite (La1-xSrxCo1-yFeyO3-δ) have recently been discovered to offer great compatibility with ceria-based electrolytes in performing as composite cathode materials for intermediate- to low-temperature SOFCs (IT-LTSOFCs). This paper reviews various ceria-based composite cathodes for IT-LTSOFCs and focuses on the aspects of progress and challenges in materials technology.